Enhancing digital engagement: The importance of media literacy in social media - Yadav, Aditi; Verma, Amit (Universitas Padjadjaran, 2025)
Background: The rapid growth of social media platforms has fundamentally changed how individuals access, create, and share information. These platforms now serve as key sources of news, entertainment, and social engagement, presenting advantages and challenges to people and communities. As social media influences public discussions and the dissemination of information, the importance of media literacy in effectively navigating the intricate digital media environment has become increasingly clear. Purpose: This study investigates the relationship between social media dynamics and media literacy, focusing on how users engage with content, develop their viewpoints, and participate in online dialogues. Methods: This research employs a multidisciplinary approach, drawing insights from communication studies, psychology, and information science to thoroughly examine the changing media landscape and its implications for democratic participation. Results: The results showed that the majority of respondents used social media daily, mainly for entertainment, while only a minority felt comfortable openly voicing opinions. Social media influences democratic engagement, affecting political and social participation, although opinion change is still variable. Media literacy awareness is low, with most relying on the credibility of sources or seeking supporting information to verify content. Conclusion: Media literacy is essential for countering disinformation, promoting critical thinking, and encouraging responsible digital citizenship. Implications: This research emphasises the importance of media literacy education to improve critical thinking, counteract disinformation, and encourage responsible digital citizenship to create a more aware and participatory democratic society.